Long-Circulating Hyaluronan-Based Nanohydrogels as Carriers of Hydrophobic Drugs - Chiara Di Meo; Mayte Martínez-Martínez; Tommasina Coviello; Marival Bermejo; Virginia Merino; Isabel Gonzalez-Alvarez; Marta Gonzalez-Alvarez; Pietro Matricardi (MDPI AG, 2018)
Nanohydrogels based on natural polymers, such as polysaccharides, are gaining interest as vehicles for therapeutic agents, as they can modify the pharmacokinetics and pharmacodynamics of the carried drugs. In this work, hyaluronan-riboflavin nanohydrogels were tested in vivo in healthy rats highlighting their lack of toxicity, even at high doses, and their different biodistribution with respect to that of native hyaluronan. They were also exploited as carriers of a hydrophobic model drug, the anti-inflammatory piroxicam, that was physically embedded within the nanohydrogels by an autoclave treatment. The nanoformulation was tested by intravenous administration showing an improvement of the pharmacokinetic parameters of the molecule. The obtained results indicate that hyaluronan-based self-assembled nanohydrogels are suitable systems for low-soluble drug administration, by increasing the dose as well as the circulation time of poorly available therapeutic agents.